Journal of African Trade - Fosu, Augustin K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of African Trade is a semi-annual publication, sponsored by the African Export-Import Bank, which seeks to publish articles that test, advance and develop models, frameworks and concepts in the broad areas of international trade and trade finance, economic growth and development, and international finance. Specifically, the journal focuses on: Theoretical issues relating to the development of trade and African trade in particular; Policy and institutional matters relating to the development of African trade and trade finance; Other contemporary issues of relevance to the development of global and African trade and trade finance. Though the foregoing constitutes the primary focus of the journal, papers relevant to trade and trade facilitation as well as other socio-economic issues, as they relate to social and economic development in Africa in general, will also be covered as the Journal of African Trade seeks to facilitate a greater understanding of the role of trade and trade-related issues in the process of economic development in Africa.
Keywords: International trade; International Trade